A routing strategy with energy optimisation based on community in mobile social networks. (6th March 2020) - Wang, Gaocai; Wang, Nao; Peng, Ying; Huang, Shuqiang
The paper proposes an optimal energy efficiency routing strategy minimised network energy consumption with a given delay based on community. Firstly, the expected energy consumption and delay of message delivery are obtained through Markov chain. Then a cost function combined with energy consumption and delay for message deliver is designed. Thus we obtain the optimisation function for delivering message of relay to comprehensive cost. Further, the reward function of relay is given. Finally, the optimal expected reward of optimal relay is achieved using the optimal stopping theory for realising the optimal energy efficiency routing strategy. In simulations, the average energy consumption, the average delay and the average delivery ratio of routing optimisation strategy are compared with other routing strategies in related literatures. The results show the proposed strategy has smaller average energy consumption, smaller average delay and bigger average delivery ratio, and better energy consumption optimisation results can be achieved.